Mathematical Modelling of Influenza-Meningitis under the Quarantine effect of influenza - Yogendra Kumar Dwivedi, Krishna Gopal Varshney, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, the effect of influenza-infected populations on the spread of meningitis is examined in the nonlinear mathematical model. Influenza only, meningitis only, influenza-meningitis infectives, quarantine influenza fraction, and recovered fractions, the population of the host is classified into six sub-classes. We have examined the locally stable model utilizing non-linear differential equations stability theory. The Basic Reproduction Number of the coinfective system grows and lowers accordingly when contact and quarantine influenza rise. As quarantine rates, recovery rate of influenza alone and influenza meningitis increases, a portion of the recovered population also rises. The model is also numerically studied for the effects of different parameters on disease propagation.